Optimizing neuronal differentiation of human pluripotent NT2 stem cells in monolayer cultures. - Abolpour Mofrad, Sepideh; Künzel, Katharina; Friedrich, Oliver; Gilbert, Daniel (Development, growth & differentiation, 2016)
Human pluripotent embryonal carcinoma (NT2) cells are increasingly considered as a suitable model for in vitro developmental toxicity and neurotoxicity (DT/DNT) studies as they undergo neuronal differentiation upon stimulation with retinoic acid (RA) and allow toxicity testing at different stages of maturation. However, differentiation of NT2 cells is not straightforward. There are different protocols available in the literature reporting varying results with regard to differentiation efficiency, expression of neuronal markers and morphological characteristics of differentiated cells. Yet, the efficiency of available protocols has not been systematically compared. To address this question, we quantified the number and size of cell cluster formed during differentiation using published and modified protocols and analyzed the abundance of neuronal and non-neuronal expression markers using immunocytochemistry. In the course of the experiments we observed that differentiation results strongly depend on the cell density at differentiation-initiation as well as on the type of used cell culture plastic ware. Based on those observations and the results from our comparative analysis, we created our own optimized and robust protocol that reproducibly reveals differentiated cells with high yield. We conclude that our method may be superior to differentiation of NT2 cells for systematic in vitro-based primary screening for developmental toxicants and neurotoxicants at different stages of maturation over previous protocols used. Our approach will also contribute to reduce animal testing in the context of the 3Rs.